Rekonsepsi Perlindungan Hukum Atas Magic dalam Perspektif Hukum Hak Cipta di Indonesia - Ayu Mustika Pamungkas (Jurnal Cakrawala Hukum, 2019)
The limitation of the form of creation protected in copyright law results in the status of works of magic being difficult to categorize even though in its development the magic is often categorized as drama or choreography, but the elements in that form do not represent magic. Protection is needed because of cases of exposure to magic tricks, while copyright law does not protect the creation in the form of methods. This certainly becomes a legal vacuum. The purpose of this study is to analyze the reconception of legal protection that is right on magic. This research is a normative juridical study with a legal, conceptual, and comparative approach. The results of the study were categorized magic as pantomime, the application of the conditions for limited protection variety arts, and the protection of magic tricks by interpreting moral rights.How to cite item: Pamungkas, A. (2019). Rekonsepsi Perlindungan Hukum Atas Magic dalam Perspektif Hukum Hak Cipta di Indonesia. Jurnal Cakrawala Hukum, 10(2), 126-136. doi:https://doi.org/10.26905/idjch.v10i2.3199